Sexual Prejudice among Puerto Rican young adults - Bauermeister, José A. (2007)
Sexual prejudice is linked to hate crimes, mental health, risk behaviors, and stigma. Few studies have examined sexual prejudice among Latinos. We surveyed 382 college students in Puerto Rico. A structural model tested whether contact and positive experiences with homosexuals, perceived similarities with peers' attitudes toward homosexuality, and religiosity were predictive of sexual prejudice among Puerto Rican young adults. Sex differences in the structural model were explored. With the exception of peers' attitudes toward homosexuality, all study variables predict sexual prejudice. No sex differences were found. Implications for decreasing sexual prejudice among Puerto Rican youth in a college setting are discussed.